'Cooperate to win': the influence of the Chilean student movement on the 2012 Budget Law. (4th March 2022) - Carvallo, Camila
ABSTRACT: In 2011, one of the most important social movements since the end of the dictatorship proposed a change in higher education in Chile. More than two hundred thousand people participated in public demonstrations. Facing the failure of the negotiations with the government, the student movement focused on proposing changes to the 2012 Budget Law. What coalitions did the leaders of this student movement form to influence the Budget Law? The aim of this paper was to analyse the factors that explain coalition formation to impact the 2012 Budget Law. In doing so, an analysis has been carried out, focusing on the leaders of the student movement (CONFECH). This paper emphasizes their coalition with the rectors of public universities and their relationship with other educational actors and the opposition parties. The analysis includes the review of documents and national newspapers and interviews with the leaders of the CONFECH. The results of the analysis show that the traditional factors explaining coalition formation are useful but not sufficient to explain the student movement alliances. This paper argues that the factor that explains the student movement coalitions is the 'strategic sense' that the movement is focused on an outcome-based strategy. The leaders consider a coalition with the rectors of public universities as outcome-tactics. However, the relationship with opposition parties was much more difficult because of their distrust resulting from what happened in 2006. This study thus has significant implications for the coalition formation theories and its relationship with social movements' impact.